Potential Beneficial Effect of Granule Organic Fertilizer (GOF) to Enhance the Growth and Productivities of Sweet Corn (Zea Mays L.) - Kurniawan, Andi; Maghfoer, Mochammad Dawam (AGRITROPICA : Journal of Agricultural Sciences, 2024)
Inorganic fertilizers have played a vital role in increasing crop production. However, its application in high doses caused adverse impacts on soil and plant production, as well as human health. The study aims to evaluate the beneficial effects of organic fertilizer in supporting sustainable plant growth and production and increasing economic value. The study was conducted from July to October 2022 in Poncokusumo, Kabupaten Malang. This study used a randomized block design (RBD) consisting of ten combination treatments with three times replication. The fertilizer combination includes GOF (250, 500, 750, and 1000 kg ha-1), Phonska (250 and 300 kg ha-1), and Urea 300 kg ha-1. Our results showed that application of GOF at a dose of 750-1000 kg ha-1 GOF + 250/300 kg ha-1 Phonska + 300 kg ha-1 Urea plays a role in increasing growth (height, number of leaves and stem diameter) and yields ha-1 sweet corn. The treatment of 1000 kg ha-1 GOF + 300 kg ha-1 Phonska + 300 kg ha-1 Urea (T8) gave the highest yield reaching 21.70 tons ha-1. The combination of GOF treatment with inorganic fertilizer (T2-T9) produces RAE values that meet the criteria for cultivation effectiveness, ranging from 128-163%. Meanwhile, the combination of 1000 kg ha-1 GOF with 300 kg ha-1 Phonska fertilizer and 300 kg ha-1 Urea (T8) fertilizer showed the highest R/C and B/C ratio values, 1.65 and 0.65. Reducing the Phonska dose by 50 kg ha-1, followed by increasing the GOF dose, can increase income. Overall, the GOF application can help increase productivity and economic benefits in sweet corn cultivation.